PENERAPAN MODEL TATA KELOLA DIGITAL PADA PELAYANAN PUBLIK DARING - Eko Prasetyo; Thita M. Mazya; Nissa Nurimani (Universitas Djuanda Bogor, 2023)
Cilegon City is one of the cities that provide online public services because it implements the smart city concept. This study aims to determine the application of the digital governance model in online public services by Cilegon City. The issue is that online public services still need to be integrated into one platform; they are not interactive services yet but are still in a one-way system. The study employs a descriptive-qualitative methodology reviewing 27 websites of regional apparatus organizations, including the Cilegon City Government website, and conducting interviews with the Heads of the Office of Communication, Informatics, Statistics, and Coding department. The study results show that the digital governance model utilized by the public service website of Cilegon City is the broadcasting model; however, only 55.4% of the criteria for implementing the broadcasting model have been met on average. Regarding implementing various digital governance models, there is no significant evidence that they have been implemented. As a result, the website for the public service in Cilegon City still delivers one-way information from public areas to broader areas, and there has yet to be significant citizen engagement as a form of participation in governance.